Analysis Methods For Memorizing Holy Qur'an In Madinatul Qur'an Islamic Boarding School - Muhammad Farid Nasrulloh; Muhammad Farid Nasrulloh; Agus Nur Ismail; Muhammad Aliyul Wafa (SCHOOLAR: Social and Literature Study in Education, 2024)
This research is motivated by the many methods of memorizing the Qur'an, in Indonesia itself there are many institutions for memorizing the Qur'an, such as Islamic boarding schools, Bayt Al-Qur'an (houses for memorizing the Qur'an), and other Tahfidzul Qur'an development institutions, and each of these institutions has different methods of memorizing the Qur'an. The Madinatul Qur'an Islamic Boarding School is a boarding school that collaborates with the Hamalatul Qur'an Jogoroto Jombang Islamic boarding school, where all the program activities are the same. This study aims to determine the method of memorizing the Qur'an in Islamic boarding schools Madinatul Qur'an. This research uses a qualitative field study approach, the data collection method is by observation, interview and documentation. The results of the research are to find out: the process of learning to memorize the Al-Qur'an, the methods used to memorize the Al-Qur'an, the supporting and inhibiting factors in memorizing the Al-Qur'an at the Islamic boarding school Madinatul Qur'an.